Sistem Informasi Pengarsipan Sertifikat Tanah pada Badan Pertanahan Nasional Aceh Besar - Yanty, Rosi Very (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
The design of the land certificate filing system was built to facilitate the work process in managing land certificate records, especially in the field of archives at the Aceh Besar National Land Agency, which is intended to streamline computerized data processing to support technical implementation in carrying out more accurate land certificate data processing, effective and efficient. A land certificate is a tool or means to convey statements or information in writing from one party to another party. Such information can be in the form of notifications, statements, requests, reports, objections, thoughts, questions, and so on. The design of the system used by the Rapid Application Development (RAD) method, a software development process model classified as incremental (multilevel) techniques. Applications used for making applications are Microsoft Visual Basic .NET as interface design and Microsoft Office Access as a DBMS. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.Keywords:Land Certificate Filing System, Information System, Visual Basic .NET